2015
DOI: 10.1007/s11606-014-3176-3
|View full text |Cite
|
Sign up to set email alerts
|

Categories of Practice Transformation in a Statewide Medical Home Pilot and their Association with Medical Home Recognition

Abstract: BACKGROUND: Healthcare purchasers have created financial incentives for primary care practices to achieve medical home recognition. Little is known about how changes in practice structure vary across practices or relate to medical home recognition. OBJECTIVE: We aimed to characterize patterns of structural change among primary care practices participating in a statewide medical home pilot. DESIGN: We surveyed practices at baseline and year 3 of the pilot, measured associations between changes in structural cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 14 publications
(20 reference statements)
0
13
0
Order By: Relevance
“…Previous studies have shown that practices in PCMH demonstrations adopt different combinations of structural characteristics. 21 A better understanding of trade-offs of structural and practice climate investments has important implications for improving quality and reducing costs for CHCs and other primary care practices.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that practices in PCMH demonstrations adopt different combinations of structural characteristics. 21 A better understanding of trade-offs of structural and practice climate investments has important implications for improving quality and reducing costs for CHCs and other primary care practices.…”
Section: Discussionmentioning
confidence: 99%
“…To assess structural transformation, we sent a survey to one leader of each practice at baseline and at the end of pilot year 3 (in each region) that queried the presence of capabilities such as patient registries, care managers, information technology, and after-hours access. 17 Based on survey responses, we calculated each practice's change on an overall structural capability score. To assess functional transformation, we measured changes in each practice's performance on quality (nine measures of chronic disease and preventive care) and costs of care over 3 years using claims data from 8 of the 12 participating health plans.…”
Section: Practice Selectionmentioning
confidence: 99%
“…Studies documenting PCMH transformation and outcomes-many of which have been federally funded-have likewise multiplied (Agency for Healthcare Research and Quality, undated-g). Findings indicate that transforming primary care is challenging (Martsolf et al, 2015;Crabtree et al, 2010). There is evidence that practices of transformation vary in how they put the concepts of PCMH into practice (Rittenhouse et al, 2013;Solberg, 2011;Tomoaia-Cotisel et al, 2016), and that implementation can improve outcomes such as cost, quality, and patient satisfaction (Friedberg et al, 2014(Friedberg et al, , 2015Strickland et al, 2011;Rosenthal, 2008;Shi et al, 2017;Farrell et al, 2015) (health care systems and services impact, patient impact).…”
Section: Patient-centered Medical Homementioning
confidence: 99%